Digital banking: Overcoming barriers to entry - MEGARGEL, Alan (Institutional Knowledge at Singapore Management University, 2018)
This dissertation examines digital banking from the perspective of two types of industry participants; non-bank FinTech alternative [substitute] financial service providers whom are intent on disrupting the market, and [incumbent] traditional banks whom are urgently pursing digital strategies in order to counteract the FinTech threat. This study is motivated by five main research questions: (1) Are FinTech firms disrupting traditional banks, and if so, what are the modes of disruption? (2) Do tradition banks view FinTech firms as a threat, and if so, what are they doing about it? (3) What are the various digital banking strategies, and how are tradition banks implementing those strategies? (4) What are the inhibitors (barriers to entry) for digital banking, and what are the challenges that traditional banks are facing to overcome these barriers to entry? (5) How can traditional banks accelerate their digital banking capability? Analysis of financial data collected on FinTech firms and banks provides supporting evidence that the FinTech threat is indeed real, that multisided platforms have the most disruptive impact, and that FinTech lending firms pose the greatest disruptive threat to traditional banks in terms of interest income. Multiple-case study analysis of eight banks reveals that legacy systems are the greatest inhibitor of digital banking capability, however banks with a high degree of service-oriented architecture (SOA) maturity can overcome this barrier. To a lesser extent, complex IT governance processes and lack of technology skills are barriers. SOA maturity is key to overcoming these barriers to entry. The contribution to practice presented in this dissertation is a proposed Digital Banking Accelerator, to help banks overcome their barriers to entry. SOA is a key enabler for digital banking. Banks with no prior SOA experience have a steep learning curve, and can take several years to fully implement an effective SOA. There are technical challenges in understanding technologies, and organisational challenges in governing decisions. The proposed Digital Banking Accelerator will essentially de-risk banks’ adoption of SOA and accelerate traditional banks’ entry into the digital banking market. The Digital Banking Accelerator is expected to reduce the implementation cycle time by at least one calendar year. The benefit of the innovation as a digital banking accelerator has already been demonstrated in the first commercial implementation.